Pedagogical strategy for lifelong learning. - Trujillo-Aguilera, F. David; Blázquez-Parra, Elidia Beatriz; Ladrón-de-Guevara-López, Isidro; Calderón-Almendros, Julián (My University, 2023)
Based on one of the fundamental principles of the educational model of the European Higher Education Area concerning the development of the capacity to achieve lifelong learning, this project has been carried out in which a set of active teaching activities have been implemented for the acquisition of key competences in the challenge of achieving one of the most important objectives that any educational system must provide: lifelong learning. The aim of this model is to facilitate the incorporation of new university graduates into the world of work. This project has been developed in the context of subjects in the field of Electronics. However, in order to facilitate transfer to other subjects, the catalogue of active teaching activities is sufficiently varied to facilitate their extrapolation and use in other subjects, thanks to the fact that teachers have a wide variety of activities to choose from. Finally, a survey has been carried out to evaluate the satisfaction, impact and improvement of this new active methodology in order to find out the students' perspectives once they have worked with this catalogue of activities.
Keywords: Enseñanza - Innovaciones; Educación permanente; Electrónica - Estudio y enseñanza permanente; LLL; Educational innovation; Teaching/learning process; Active methodologies; Electronics